Case report: giant cell arteritis in a patient with carotid atherosclerosis - a diagnostic dilemma - Beenish Fayyaz (Greater Baltimore Medical Center, 2018)
Carotid atherosclerosis and giant cell arteritis (GCA) are two distinct medical conditions with an overlapping clinical spectrum of vascular symptoms such as vision loss and ischemic stroke. This is because both diseases cause arterial ischemia with a predilection for carotid vasculature. In addition, high-vascular risk individuals who are diagnosed with GCA are usually elderly with age >55 years with high-vascular risk and thus can have underlying atherosclerosis. All these factors can pose a diagnostic dilemma for the physicians as GCA is a medical emergency which if left untreated can result in significant morbidity and mortality. Thus, it is important to avoid attributing occlusive arterial disease in elderly patients to atherosclerosis alone because some may have GCA. We present a case report in which presence of diffuse atherosclerosis was a major pitfall while making a timely diagnosis of GCA.